Physical activity cut-points for older adults using the Zio XT onboard accelerometer - Etzkorn, Lacey H.; Davoudi, Anis; Dooley, Erin E.; Gabriel, Kelley P.; Chen, Lin Yee; Crainiceanu, Ciprian M.; Schrack, Jennifer A.; Wanigatunga, Amal A. (BMC Digital Health, 2024)
Introduction The Zio® XT continuous ambulatory electrocardiographic monitor (Zio) contains an accelerometer that can help quantify an individual’s physical activity in the free-living environment. Purpose (1) To estimate activity cut-points to estimate daily time spent performing very light, light, or moderate to vigorous physical activity (VLIPA, LIPA, MVPA) for the Zio accelerometer. (2) To describe how Zio’s 24-h wear protocol affects estimates of daily MVPA relative to a waist-worn accelerometer’s waking-wear protocol. Methods Three hundred eighty one participants from the Atherosclerosis Risk in Communities (ARIC) study wore a waist-mounted ActiGraph GT3X (except while sleeping or water-based activities) and a Zio (24-h) simultaneously for three to seven days. For each person-minute, physical activity was summarized as the Mean Amplitude Deviation (MAD) for the Zio and Vector Magnitude Counts (VMC) for the GT3X. Cut points previously used in ARIC were mapped from GT3X VMC to Zio MAD using a conditional two-sample quantile–quantile approach. Results Evenson VMC cut-points for the GT3X (VLIPA≥76, LIPA≥903, MVPA≥2075 counts/min) were mapped to MAD for Zio (9.04, 28.2, and 58.1 mili-g). Daily hours spent in each intensity category were each strongly correlated (ICC > 0.7) between summaries produced by Zio and GT3X when restricting estimates to overlapping wear time. Zio and GT3X-estimated MVPA had high agreement (ICC = 0.77) when using device-specific wear time, but Zio measured one hour more of daily LIPA and VLIPA (95% CI = 0.83, 1.07 hrs/day). Conclusions We recommend the use of our cut-points for clinical research with Zio accelerometry in populations of older adults.